Welsh saints on the Mormon Trail: the story of the Welsh emigration to Salt Lake City during the Nineteenth century - Aaron, Wil (Y Lolfa, 2019)
"Between the mid 1840s and late 1860s, around 5,000 Welsh people, inspired by the Mormon faith, ventured to start a new life in the United States...seeking their holy city in the West..."--back cover